Molecular phylogeny and higher systematics of the metalmark butterflies (Lepidoptera: Riodinidae). (11th January 2018) - SERAPHIM, NOEMY; KAMINSKI, LUCAS A.; DEVRIES, PHILIP J.; PENZ, CARLA; CALLAGHAN, CURTIS; WAHLBERG, NIKLAS; SILVA‐BRANDÃO, KARINA L.; FREITAS, ANDRÉ V.L.
Abstract: Riodinidae is a highly diverse butterfly family with the majority of its genera restricted to the Neotropics and, despite previous efforts, its higher systematics remains unresolved. Here, we propose a novel phylogenetic hypothesis, based on a comprehensive sample of riodinids, primarily from the Neotropics, covering 67% of all genera and all of the major lineages. We sequenced nine molecular markers and estimated resulting phylogenies with maximum likelihood and Bayesian approaches, using both timed trees and time‐independent trees. We based calibration on three fossil Riodinidae, and reassessed the position of the oldest fossil. We also incorporated 52 samples from a previous study providing a comprehensive maximum likelihood tree for 304 species comprising 80% of all genera. We propose a new higher classification of the Riodinidae with two subfamilies: the Nemeobiinae, including the Old World riodinids and their Neotropical sister Euselasia Hübner; and the Riodininae, comprising all remaining genera. We divided Riodininae into nine tribes (including four new tribes: Calydnini Seraphim, Freitas & Kaminskitrib.n. ; Sertaniini Seraphim, Freitas & Kaminskitrib.n. ; Dianesiini Seraphim, Freitas & Kaminskitrib.n. ; and Emesidini Seraphim, Freitas & Kaminskitrib.n. ), with Mesosemiini and Nymphidiini further subdivided into two and seven subtribes (including three new subtribes for Nymphidiini: Zabuellina Seraphim, Freitas & Kaminskisubtrib.n. ; Pachythonina Seraphim, Freitas & Kaminskisubtrib.n. ; and Pandemina Seraphim, Freitas & Kaminskisubtrib.n. ). Although our phylogenetic hypotheses are generally congruent with the analyses by Espeland et al. (2015), the comprehensive taxon sampling employed here constitutes a large step towards a stable tribal‐level classification. All taxonomic changes are summarized in a checklist. Despite most genera being restricted to tropical South and Central America, the oldest known fossil of Riodininae belongs to the Green River formation (42.6–50.2 Ma) in North America. Accordingly, we reassess the family's crown age at 56 Ma (52.4–60.7 Ma), which is at variance with previous dating using secondary calibrations and a different subset of genes. Nonmonophyletic riodinid genera are ubiquitous, and several groups need further revision, including groups revised recently. Our results point to the need for integrative taxonomy, as adult morphology seems to be have been exhausted as a single data source in this family. This published work has been registered on Zoobank, http://zoobank.org/urn:lsid:zoobank.org:pub:BCA2DDC5‐753B‐4178‐8E7B‐B7ED1E995CE8 . Abstract : This is the most comprehensive molecular phylogeny of metalmark butterflies to date, including extensive Neotropical sampling and covering 304 species, 80% of genera and all major lineages. We revise higher systematics, describing four new tribes, three new subtribes and providing a checklist summarizing all changes. The position of the oldest fossil ( Riodinella nympha ) is reassessed and the family's crown age is estimated at 56 Ma, suggesting that riodinids were the latest butterflies to diversify.